2005
DOI: 10.1080/03079450500268328
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of and susceptibility to malabsorption syndrome in broilers is associated with heterophil influx into the intestinal mucosa and epithelial apoptosis

Abstract: Malabsorption syndrome (MAS) in broilers is characterized by enteritis and reduced body weight gain. The pathogenesis of the intestinal lesions and the reasons for susceptibility differences between broiler lines are not clear. We studied the development of enteric lesions, epithelial apoptosis, and cell proliferation in relation to susceptibility. One-day-old chickens from two broiler lines were orally inoculated with intestinal homogenate derived from MAS-affected chickens. Vacuolar degeneration and apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 25 publications
3
21
1
4
Order By: Relevance
“…From the T-cell profiles together with the cytokine mRNA profiles of the intestines it was concluded that the susceptible line reacted with a more cell mediated T-helper response to a MAS infection compared to the "resistant" line. This is in agreement with the recruitment that was observed of cytotoxic T-cells and heterophils (Songserm et al, 2002a;Zekarias et al, 2005). Such insufficient or uncontrolled reactivity at the mucosal surfaces might lead to the severe damage that was observed in the intestine of the sensitive line.…”
Section: Immune Responsesupporting
confidence: 89%
See 2 more Smart Citations
“…From the T-cell profiles together with the cytokine mRNA profiles of the intestines it was concluded that the susceptible line reacted with a more cell mediated T-helper response to a MAS infection compared to the "resistant" line. This is in agreement with the recruitment that was observed of cytotoxic T-cells and heterophils (Songserm et al, 2002a;Zekarias et al, 2005). Such insufficient or uncontrolled reactivity at the mucosal surfaces might lead to the severe damage that was observed in the intestine of the sensitive line.…”
Section: Immune Responsesupporting
confidence: 89%
“…In another study Zekarias et al (2005)showed that in the onset of MAS there was an association between heterophil influx and the onset of apoptosis of the crypt epithelium. MAS induced chickens showed crypt hyperproliferation and increased epithelial turnover.…”
Section: Mas Susceptibilitymentioning
confidence: 93%
See 1 more Smart Citation
“…Ten age-matched control birds received 0.2 ml of vaccine diluent. After 4 wk, turkeys were challenged with 2 3 10 6 50% embryo infectious doses (EID 50 ) per bird of the SM05 pathogenic virus delivered intranasally. The challenge dose was equivalent with 2000 of the 50% bird lethal doses.…”
Section: Methodsmentioning
confidence: 99%
“…Porém, existem ainda várias condições negativas que podem resultar em problemas entéricos em frangos de corte, que afetam a digestão de nutrientes da dieta, o equilíbrio da microbiota intestinal e, consequentemente, os parâmetros de produção (Zekarias et al 2005, Teirlynck et al 2011.…”
Section: Introductionunclassified